Culture and self-construal in the age of globalization: an empirical inquiry based on multiple approaches - Li, Kang; Wang, Fengyan; Pi, Zhongling (Frontiers in Psychology, 2024)
Introduction There are three main types of culture in human society, namely, individual-oriented, relationship-oriented and social-oriented cultures. In history, there are two main positions on the relationship between culture and self-construal: the cultural determinist position and the interaction position. After analyzing literature critically, we propose that the interaction position is more persuasive than the cultural determinist position. A self-construal model was constructed from an interactionist and polycultural perspective, pointing out the relationship between three cultures and self-construal. We argue that individuals interacting with cultures in the context of globalization can develop a more integrated self-construal. The present study proposes the existence of polycultural self-construal, and aimed to explore how self-construal factors relate to cultures. Methods Three approaches—psychological tests, priming with cultural icons and content analysis—were used to explore mechanisms between cultures (individual-oriented, relationship-oriented, and social-oriented cultures) and self-construal. In Study 1, we recruited 460 undergraduate students as participants through campus advertising to complete three psychological tests, namely, the Cultural Identity Scale (CIS), the Marlowe-Crowne Social Approval Scale (MC-SDS), and the Polycultural Self-construal Scale (PSCS). In Study 2, we created icon materials that could prime the three cultures. The experimental process was divided into two stages: priming and measurement. First, 165 participants were presented with icon materials on the computer screen to activate the corresponding culture, and then they were asked to complete the PSCS. In Study 3, the experimental procedures were followed as for Study 2. Then the Ten Statements Test (TST) was used. Each of the 178 participants gave 10 different responses to the question of “Who am I?.” Each participant’s “I am …” narratives were qualitatively processed using content analysis. Results The individual-oriented culture mainly affects the individuality and equality factor of self-construal. The relationship-oriented culture mainly impacts the relationality factor of self-construal, while the social-oriented culture mainly affects the collectivity and equality factors of self-construal. There were no significant differences in the effects of the three cultures on the autonomy factor of self-construal. The multi-components of the polycultural self-construal are difficult to interpret based on one culture type. All three cultures have specific and shared effects on human self-construal.